2020
DOI: 10.3390/soilsystems4020031
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Mobile Gamma Spectrometry as Tool for Precision Farming and Field Experimentation

Abstract: Soils naturally emit gamma radiation that can be recorded using gamma spectrometry. Spectral features are correlated with soil mineralogy and texture. Recording spectra proximally and in real-time on heterogeneous agricultural fields is an option for precision agriculture. However, the technology has not yet been broadly introduced. This study aims to evaluate the current state-of-the art by (i) elucidating limitations and (ii) giving application examples. Spectra were recorded with a tractor-mounted spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…With this goal in mind, the multidisciplinary project consortium, "Intelligence for Soil (I4S)-Integrated System for Site-Specific Soil Fertility Management", funded within the German national program "Bo-naRes: Soil as a Sustainable Resource for the Bioeconomy", is seeking to develop an integrated sensor system for in situ field application by combining a range of complementary measurement techniques with individual benefits. Selected atomic spectroscopic methods include X-ray fluorescence, 10 laser-induced breakdown spectroscopy, [11][12][13] or gamma spectroscopy, 14,15 whereas molecular spectroscopic techniques comprise mid-infrared, 4 near-infrared, 16 and Raman spectroscopy. 17 While atomic spectroscopy can reveal the total mass fractions of elements, their binding form within the soil cannot be determined by such methods.…”
Section: Introductionmentioning
confidence: 99%
“…With this goal in mind, the multidisciplinary project consortium, "Intelligence for Soil (I4S)-Integrated System for Site-Specific Soil Fertility Management", funded within the German national program "Bo-naRes: Soil as a Sustainable Resource for the Bioeconomy", is seeking to develop an integrated sensor system for in situ field application by combining a range of complementary measurement techniques with individual benefits. Selected atomic spectroscopic methods include X-ray fluorescence, 10 laser-induced breakdown spectroscopy, [11][12][13] or gamma spectroscopy, 14,15 whereas molecular spectroscopic techniques comprise mid-infrared, 4 near-infrared, 16 and Raman spectroscopy. 17 While atomic spectroscopy can reveal the total mass fractions of elements, their binding form within the soil cannot be determined by such methods.…”
Section: Introductionmentioning
confidence: 99%
“…The detector, positioned 30 centimeters above the ground, measures soil gamma rays with a radius of approximately 2 meters and a depth of 0.3 meters. The accuracy of both measurements is almost the same (R 2 = 0.96) [3]. The detectors used for PMGS include a 1 to 2 × 4.2 L NaI detector [3,24,26] and a φ70 × 150 mm CsI detector [45], among others.…”
Section: Device For Car-borne and Agricultural Tractors Surveymentioning
confidence: 99%
“…The accuracy of both measurements is almost the same (R 2 = 0.96) [3]. The detectors used for PMGS include a 1 to 2 × 4.2 L NaI detector [3,24,26] and a φ70 × 150 mm CsI detector [45], among others. The running speed for the on-the-go survey is applied at 0.7 to 1.4 meters per second [3], 0.83 meters per second [26], and 2.8 meters per second [45].…”
Section: Device For Car-borne and Agricultural Tractors Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Rudolph et al (2016) demonstrated the statistical advantage of using ECa readings as continuous covariates in regression models over the "improved blocking" strategy. Moreover, the authors recommended the use of additional sensors such as gamma ray to improve statistical models (Pätzold et al, 2020). In addition, the comparison of different experimental designs with and without spatial information showed that including spatial covariates reduced Type I error regardless of the design and D.W. Raffa et al randomization (Alesso et al, 2019).…”
Section: Introductionmentioning
confidence: 99%